Embryological analysis of Consolida regalis L. (Ranunculaceae) - (:unkn) unknown (POLSKA AKADEMIA NAUK, 2006)
In Consolida regalis L. the development of the embryo sac conforms to the Polygonum type. In the mature embryo sac, the egg apparatus and secondary nucleus are of normal appearance. The synergids are ephemeral and disappear soon after fertilization. The antipodal cells are large and persistent but remain uninucleate and show rhythmical growth. The volumes of antipodal nuclei correspond with ploidy levels from n to 256n. Cytochemical tests indicate the presence of high amounts of proteins, lipids, polysaccharides, RNA and DNA in the antipodals. They degenerate in the cellular endosperm stage. The endosperm is nuclear; centripetal wall formation starts at the micropylar end and progresses towards the chalaza. Embryogeny is of the Solanad type. The mature embryo lacks organs at shedding of seeds.
Keywords: Consolida regalis; Ranunculaceae; embryo sac; antipodals; endoreduplication; embryo; endosperm; ANTIPODALS; ENDOPOLYPLOIDY; POLYPLOIDIZATION